1997
DOI: 10.1111/j.1475-2743.1997.tb00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural soils as a sink to mitigate CO2 emissions

Abstract: Abstract. Agricultural soils, having been depleted of much of their native carbon stocks, have a significant CO2 sink capacity. Global estimates of this sink capacity are in the order of 20‐30 Pg C over the next 50‐100 years. Management practices to build up soil C must increase the input of organic matter to soil and/or decrease soil organic matter decomposition rates. The most appropriate management practices to increase soil C vary regionally, dependent on both environmental and socioeconomic factors. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
442
2
16

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 807 publications
(473 citation statements)
references
References 93 publications
13
442
2
16
Order By: Relevance
“…Working Group III also stated the high agreement and much evidence that soil carbon sequestration is the mechanism responsible for most climate change mitigation potential (Paustian et al, 1997). The IPCC's AR4 Synthesis Report confirmed that effective carbon-price signals can mobilise environmentally effective mitigation options in the agriculture and forestry sectors, including as improved land management practices that maintain soil carbon density and for soil carbon sequestration.…”
Section: Introductionmentioning
confidence: 95%
“…Working Group III also stated the high agreement and much evidence that soil carbon sequestration is the mechanism responsible for most climate change mitigation potential (Paustian et al, 1997). The IPCC's AR4 Synthesis Report confirmed that effective carbon-price signals can mobilise environmentally effective mitigation options in the agriculture and forestry sectors, including as improved land management practices that maintain soil carbon density and for soil carbon sequestration.…”
Section: Introductionmentioning
confidence: 95%
“…Sistemas de manejo que aumentem a adição de resíduos vegetais e a retenção de C no solo se constituem em alternativas importantes para aumentar a capacidade de dreno de C-CO 2 atmosférico e mitigação do aquecimento global (Amado et al, 2001;Bayer et al, 2006). Várias são as ênfases e as formas de quantificar o efeito de sistemas de manejo sobre os fluxos de C no sistema solo-planta-atmosfera citadas na literatura (Paustian et al, 1997;Janzen et al, 1998). O balanço de C no solo é dependente da relação entre as adições de C fotossintetizado pelas plantas (parte aérea e raízes) e as perdas de C para a atmosfera resultantes da oxidação microbiana do C orgânico a CO 2.…”
Section: Introductionunclassified
“…The type of plants cultivated and their sequence in the crop rotation influences soil Eh and pH for two reasons: (i) plants and their associated microorganisms play a crucial role in the formation and alteration of soil (Lambers et al 2009); and (ii) plant biomass production and inputs to the soil influence soil organic matter content, which buffers the Eh and pH of the bulk soil (Paustian et al 1997). In the surface horizon (0-30 cm) of an aerobic soil, Bohrerova et al (2004) measured significant soil Eh differences between cropping systems, with a higher Eh on an alfalfa/wheat rotation than on a sugar beet/barley rotation.…”
Section: Impacts Of Agricultural Practices On Soil Eh and Phmentioning
confidence: 99%